Strength by overcoming - McIlvaine, Robert A. (My University, 1892)
Introduction: As we leave the work where we have been led by those more experienced in the results of labor and go to fields where must set the tasks for ourselves and sometimes for others, we are forced to consider what course of action will lead to the greatest development and be most useful to all concerned. When full freedom comes to the youth his position is one of peril. Until now he has been directed in the management of his time; he has had to labor at home and school, willingly or unwillingly. But now the bonds are loosed, and he is at liberty to go wherever he desires and do whatever he thinks best. Shall he toil on as before or shall he seek the paradise that ease and pleasure seem to have given to others? This question so easy of answer to him whom years of experience disciplined, is perplexing to the one who stands at the parting of the ways with little knowledge of the destination of either. He hears the siren voice of pleasure, “Come with me and rest: why should you vex yourself with care and toil? Did not the wise man say that all is vanity? Why then waste life away for something that can never satisfy?” How tempting is the call to one who feels that labor is a curse to mankind; but if he heeds and follows will he find the ease and satisfaction promised?
Citation: McIlvaine, Robert A. Strength by overcoming. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Labor; Strength; Overcoming; Temptation; Work force; Sociology; Theses; Manuscripts (documents)